PENGARUH LATIHAN FISIK AEROBIK DENGAN INTENSITAS SEDANG TERHADAP KONDISI MAKROSKOPIK DAN GAMBARAN HISTOPATOLOGI MIOKARD MENCIT BALB/C - Niswan Helja Batubara; Nova Sylviana; Hasrayati Agustina; Hadaral Hudanul Qolbi (PAIFORI, 2019)
Cardiovascular diseases is one of the non-communicable diseases that has been the leading cause of death compared to other causes. Actually, cardiovascular diseases can be prevented with avoiding the risk factors and lifestyle improvements such as doing physical exercise. Useful physical exercise according to according to The American College of Cardiology/American Heart Association (ACC/AHA) is a moderate intensity aerobic exercise conducted 30 minutes in time for 5 days a week. This research aims to study the effects of moderate intensity aerobic exercise on macroscopic conditions, histopathologic features of the myocardium of mice. This research using 35 male balb/c mice devided to 3 groups (control, physical activity, exercise). Variables in this research included duration of physical activity and exercise, macroscopic conditions, histopathologic features of the myocardium of balb/c mice. After 10 and 28 days of exposure, the heart were harvested. The macroscopic conditions, histopathologic features of the myocardium were examined. The weight of heart in physical activity group was greater than control group (p=0.009). Similarly, the weight of heart exercise group was also greater compared to control group (p=0.013). The histopathologic features in physical activity and physical exercise groups showed pathological features of myocardial infarction (p=0.242). While in the control group did not show pathological features. Aerobic physical activity moderate intensity increase the risk of pathological condition of heart in the form of myocardial infarct through the macroscopic conditions and histological features of myocardium. Meanwhile, exercise with moderate intensity affect the physiological hypertrophy of the myocardium.